Sulphur K-edge XANES spectroscopy of transthyretin amyloid fibres. Issue 3 (2002) - Gales Gales, L. L.; Cardoso Cardoso, I. I.; Fayard Fayard, B. B.; Saraiva Saraiva, M.J. M.J.; Damas Damas, A.M. A.M.
Abstract : Transthyretin (TTR) amyloidosis results from the self‒association of TTR leading to insoluble deposits that occur at the extra cellular level. Sulphur K‒edge XANES spectroscopy was used to determine the sulphur oxidation state in transtyretin present in amyloid fibrils. These data is discussed in relation to molecular mechanisms involved in amyloid fibril formation.